Relationships of Nerve Conduction Parameters with the Thyroid Hormones in Hypothyroid Patients - Yeasmin, Sabina; Begum, Noorzahan; Begum, Shelina; Rahman, Shah Mohammed Hafizur (Journal of Bangladesh Society of Physiologist, 2013)
Background: Impairment of nerve conduction may occur in hypothyroidism which usually develops insidiously over a long period of time due to irregular taking of drugs or lack of thyroid hormone replacement. Objectives: To evaluate the thyroid hormone status and the clinical and electrophysiological changes in hypothyroid patients in order to observe their relationships with nerve conduction changes. Methods: Thirty healthy euthyroid subjects with the age range from 20 to 50 years of both sexes were as control and 15 hypothyroids with TSH with <60 MIU /L and the duration of 6 months to 5 years were as experimental. Serum TT3, TT4 were measured by RIA and IRMA method. The distal latency (D L) and Nerve Conduction Velocities (NCV) for sensory and motor function were measured by a standard electrophysiological technique in median and ulnar nerve for upper limb and for lower limb, in sural nerve for sensory function and common peroneal nerve for motor function. Data were analyzed statistically by unpaired t test, Z test, Pearsons correlation coefficient test. Results: Both TT3, TT4 levels were significantly (P<0.001) lower in hypothyroids. Again, 60% hypothyroids and 10% euthyroids (P<.001) had abnormal NCV. The relationships of TSH with both the median and ulnar sensory and motor distal latencies, common peroneal motor and sural sensory distal latencies and ulnar sensory conduction velocity were positive. But these relationships were negative with the median and common peroneal motor nerve conduction velocities, sural sensory conduction velocities. Only the relationships between median sensory distal latency and TSH was statistically significant (P <0.05). Again, a positive correlation of TT3 and TT4 with the median, and sural sensory and common peroneal motor conduction velocities, but negative correlation with median motor and sural sensory latencies were found. In addition, positive correlation between TT3 and ulnar sensory and between TT4 and Ulnar motor conduction velocities were observed. Again the relationships median and ulnar sensory latencies were negative with TT4 only. The value of coefficient between TT4 and sural distal latency and conduction velocities were statistically significant (P<0.05). Conclusion: Results of this study showed that the impairment of nerve conduction occurs in hypothyroidism. DOI: http://dx.doi.org/10.3329/jbsp.v8i1.16638 J Bangladesh Soc Physiol. 2013, June; 8(1): 1-5